2002
DOI: 10.1345/aph.1a143
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Colesevelam Hydrochloride in Healthy Volunteers

Abstract: The cumulative recovery data in urine and feces are consistent with the conclusion that colesevelam is not absorbed and is excreted entirely through the gastrointestinal system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The methodology for characterizing plasma drug content is irrelevant as resins rarely appear as such in blood circulation and are not easily characterizable as a drug entity because of their very large molecular weight and polydisperse nature; more typically impurities and degradation products are first identified in stress-stability testing or in vitro metabolism studies and then monitored in plasma. However, the gold standard method remains radioactive labeling with 14 C and measuring the distribution of the label in urine, feces, and body tissues; typically synthetic crosslinked resins are almost quantitatively recovered in the feces, with yields ranging from 82% [11] to 99% [12]. Certain sequestering materials are made of insoluble metallic inorganic materials that release soluble metallic salts (Fe, Mg, La), which can potentially be absorbed.…”
Section: Non-absorption Criteria Across Classes Of Non-absorbable Drugsmentioning
confidence: 99%
“…The methodology for characterizing plasma drug content is irrelevant as resins rarely appear as such in blood circulation and are not easily characterizable as a drug entity because of their very large molecular weight and polydisperse nature; more typically impurities and degradation products are first identified in stress-stability testing or in vitro metabolism studies and then monitored in plasma. However, the gold standard method remains radioactive labeling with 14 C and measuring the distribution of the label in urine, feces, and body tissues; typically synthetic crosslinked resins are almost quantitatively recovered in the feces, with yields ranging from 82% [11] to 99% [12]. Certain sequestering materials are made of insoluble metallic inorganic materials that release soluble metallic salts (Fe, Mg, La), which can potentially be absorbed.…”
Section: Non-absorption Criteria Across Classes Of Non-absorbable Drugsmentioning
confidence: 99%
“…Kinetic studies performed in healthy adult volunteers have shown that colesevelam is a hydrophilic, insoluble polymer with minimal systemic absorption and distribution 32. After administration of a single dose of [ 14 C]-colesevelam to 16 healthy adult volunteers after receiving 28 days of colesevelam 1.9 g twice daily, the maximum detectable plasma concentration 72 hours after administration was 0.04%, consistent with residual [ 14 C].…”
Section: Pharmacokineticsmentioning
confidence: 64%
“…1,6 Colesevelam HCI is not absorbed from the intestine. 7 In pharmacokinetic studies, colesevelam HCl did not demonstrate clinically significant interactions with several drugs that are often prescribed concomitantly in patients who require cholesterol-lowering pharmacotherapy (e.g., lovastatin, fenofibrate, warfarin, digoxin, metoprolol). [8][9][10] By contrast, conventional BAS have been shown to interfere with the pharmacokinetics of several other drugs, including warfarin, [11][12][13] thiazide diuretics, 14,15 cardiac glycosides, 16,17 and propranolol.…”
Section: Introductionmentioning
confidence: 93%